P-468 Organotypic culture of testicular tissue from infant boys with cryptorchidism. (30th June 2022) - Wang, D; Hildorf, S; Ntemou, E; Dong, L; Pors, S; Mamsen, L; Fedder, J; Hoffmann, E; Clasen-Linde, E; Cortes, D; Thorup, J; Andersen, C
Abstract: Study question: Can organotypic culture support the survival and maturation of germ cells and niche-related cells within testicular tissue from infant boys with cryptorchidism? Summary answer: The testicular structure and the number of germ cells were maintained during organotypic culture, whereas Sertoli cells and peritubular myoid cells (PTMCs) matured. What is known already: Testicular tissue cryopreservation (TTC) is a strategy to safeguard the fertility of prepubertal boys who face a risk of infertility. Organotypic culture of immature testicular tissue from mice achieved production of spermatozoa. Similarly, the culture of human fetal gonads resulted in the generation of competent spermatids. However, in vitro spermatogenesis by organotypic culture of human prepubertal testicular tissue has not been achieved. It is also unknown whether germ cells as well as its niche-related cells, in testicular tissue from infant boys with cryptorchidism, can maintain and mature under in vitro conditions. Study design, size, duration: Testicular tissue was cryopreserved from four infant boys with bilateral cryptorchidism undergoing orchidopexy (age range: 0.5-1.4 years), as part of a fertility preservation program. Culture media with and without retinoic acid were tested. Testicular fragments were harvested at 30 days and 60 days after culture and evaluated by histological assessment of tissue structure, germ cell development, and immunohistochemical staining for germ cell and somatic cell markers. Participants/materials, setting, methods: Cryopreserved-thawed testicular tissue was cut into fragments (1-2 mm 3 ) and placed on top of agarose gel stands and cultured at 34 o C with 5% CO2 in Minimum Essential Medium-alpha supplemented with knockout serum replacement, human umbilical cord plasma, Activin A, hormones, growth factors, with or without retinoic acid. Immunohistochemical analyses were performed using germ cell markers (MAGE-A, GAGE, and VASA), Sertoli cell maturation markers (AMH, AR, SOX9), PTMC marker (alpha-SMA). Main results and the role of chance: Following the 60-day culture, the lumen of the seminiferous tubules had developed. The number of germ cells per tubule remained stable during this period. However, no further germ cell maturation was observed. Germ cells showed different phenotypes of MAGEA, GAGE, and VASA expression with no significant difference in number. The number of SOX9-positive Sertoli cells was significantly increased from 30 days to 60 days of culture ( p <0.0001). No difference in AMH expression was observed, while AR expression in Sertoli cells was induced during culture. Alpha-SMA expression was detected in the PTMCs surrounding the seminiferous tubules. The two different culture conditions, with and without retinoic acid in the culture media, did not affect cell survival or maturation. Limitations, reasons for caution: The small number of testicular biopsies available is a limitation. Wider implications of the findings: Our organotypic culture conditions support the long-term survival of germ cells in testicular tissue from infant boys with cryptorchidism. Thus, further studies are needed to induce the maturation of germ cells under similar experimental conditions. Trial registration number: not applicable